Pemberdayaan Masyarakat Melalui Program Basic Safety Training (BST) bagi Siswa SMK Negeri 4 Purworejo - Suganjar Suganjar; Heru Widada (Sejahtera: Jurnal Inspirasi Mengabdi Untuk Negeri, 2025)
Basic Safety Training (BST) is a basic safety training that must be had by every crew member before working on a ship. This activity aims to equip prospective sailors with the basic safety knowledge and skills needed to deal with emergency situations on board. This activity is carried out using the participatory action research (PAR) method approach and hands-on training method. The stages of implementation include the Preparation and Planning Stage, the Training Implementation Stage, and Evaluation. The implementation of this activity provides material on potential hazard identification, risk mitigation, and standard safety procedures according to international regulations. Survival techniques at sea, the effects of hypothermia, energy conservation strategies, and ship evacuation procedures according to STCW standards. Fire prevention and fire classification. This program strengthens the relevance of the curriculum to industry needs and enhances the reputation of SMK as a provider of quality maritime workers. It can be concluded that the implementation of the program with a comprehensive learning method that combines theory and practice in a balanced manner has proven effective in providing knowledge and skills to participants.